Sudden Death Due to Undiagnosed Rheumatic Heart Disease in a Child1. Issue 3 (15th February 2016) - Rérolle, Camille; Faisant, Maxime; Lefrancq, Thierry; Saint‐Martin, Pauline
Abstract: We report the case of a 5‐year‐old boy who died from complications of rheumatic heart disease with atypical presentation. He was hospitalized for recent inflammatory and neurological symptoms. He was diagnosed with viral encephalitis. He died the day after he was discharged. The macroscopic autopsy findings were unremarkable. Histology revealed typical rheumatic heart disease. Neuropathology showed cerebral infarction due to an embolic event linked with the rheumatic valvulitis. The cause of death was determined as heart failure due to rheumatic heart disease secondary to an undiagnosed acute rheumatic fever. It is related to an autoimmune response to infection with group A streptococcus. It mainly affects children in developing countries. In our case, viral encephalitis was consistent with the medical history and the proper diagnosis was made on histological analysis. Forensic pathologists should consider this diagnosis facing a sudden unexpected death in childhood, even in industrialized countries.